تأثيرنموذج فكر وزاوج وشارك في تنمية مهارة الكلام لدي طلاب المدرسة الثانوية الإسلامية - Suci Nur Anggraini; Mulyadi; Agung Yusup ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2026)
This study aims to determine the effect of the Cooperative Learning model, specifically the Think Pair Share (TPS) type, on students’ speaking skills (maharah al-kalam). This research used a quantitative approach with a quasi-experimental design, namely the pretest-posttest control group design. The sample consisted of two classes: an experimental class and a control class, with a total of 28 students. Data were collected through tests (pretest and posttest) and documentation. Data analysis included normality test, homogeneity test, and hypothesis testing using independent sample t-test. The results showed that the post-test mean score of the experimental class was higher than that of the control class. The hypothesis test result indicated a significance value of < 0.05, meaning that TPS had a significant effect on students’ speaking skills. TPS proved effective in improving students’ participation, confidence, and speaking fluency.